Effectiveness of Communication, Information and Education Responsive Feeding the Knowledge, Attitudes and Skills in the provision of complementary feeding mother Toddlers and Weight Gain - Heni Hendriyani; Wiwik Wijaningsih; Muflihah Isnawati (Jurnal Riset Kesehatan, 2013)
Background: In indonesia, stunted, waste and undernutrition  children remain nutrition problems. Primary health survey indicated that as many as 35,6% under five children were stunted, 13,3% waste and 17,9 were undernutrition. Objective: to investigate the effect of KAP (knowledge, attitude and practice) of responsive feeding  intervention on complementary feeding and children’s weight.Methods: the study used quasi experiment design. There were 70 children on both groups. Intervention group was given 3 times counselling, home visit completed with video, brochures, and modul,  meanwhile comparative group was given general health information.Results: the study showed that responsive feeding intervention through communication, information and  education has positif effect on the responsive feeding practice (p=0,001) yet did not at knowledge, attitude toward responsive feeding (p=0,905 dan p=0,728) and the increase of children’s weight (p=0,402).